ANALISA PROSES MANUFAKTUR MESIN PRESS LEMBARAN (SHEET PRESS MACHINE) DARI SAMPAH PLASTIK MENGGUNAKAN METODE DESIGN FOR MANUFACTURE AND ASSEMBLY (DFMA) - Muhammad Roja Qashmal, (2021)
Plastic waste has been a major problem in the environment, both land and sea pollution. The nature of plastic that is difficult to decompose and the increasing use of single-use plastics cause the amount of plastic waste to increase from time to time. The importance of recycling plastic waste into useful items can certainly contribute to reducing the amount of plastic waste in the environment. This underlies the author to design a tool that can optimize the sheet press machine using DFMA. This method was chosen by the author in order to reduce assembly time and reduce production costs. This sheet press machine can produce a plastic sheet with a size of 90 cm x 50 cm x 1 cm. The results showed that the press machine that was created was able to produce a higher efficiency level of 2.4% and had a much cheaper price than the machines already sold in the market.